The effects of corporate social responsibility (Csr) on corporate brand positioning - Makasi, Africa; Govender, Krishna; Munyoro, Tendai (MCSER Publishing, 2021)
The purpose of this paper was to investigate the role of Corporate Social Responsibility (CSR) in corporate brand positioning in the printing and packaging industry in Zimbabwe. The research was conducted by reviewing various streams of literature and interviews with 10 representatives from 5 companies and 10 customers also participated in this research. A semi-structured questionnaire was used. Two representatives from each of the ten competing companies were selected while customer representatives (both industrial and ordinary) were selected using the companies’ customer records as the sampling frame. These were selected on the basis of the ratio of their revenue contribution which stands at 1: 2 in favour of industrial customers. All qualitative responses were grouped into themes for coding purposes. The data gathered was coded and captured to form panel data for further analysis using the Statistical Package for Social Sciences (SPSS) version 19. Results of the research indicated that15 out of the sampled respondents of 20 confirmed that indeed CSR directed towards employees through provision of health care services and education and other activities as highlighted help to improve corporate image and position. The research also concluded that communities are intertwined with companies and their perceptions matter in corporate brand positioning. Using results of the T-Tests, it was concluded that CSR programs directed towards the environment play an important role in positioning corporate brands. Future research can refine CSR input by recognizing these differences and theorizing about employees’ reactions.